The immediate and delayed effects of direct versus indirect written corrective feedback on Turkish EFL learners' accuracy development in using past counterfactual conditionals - Uludağ, Onur (Lesya Ukrainka Volyn National University, 2025)
Written corrective feedback (WCF) research has extensively examined the effectiveness of direct versus indirect feedback approaches, yet findings remain inconsistent regarding their relative impact on complex grammatical structures. The acquisition of past counterfactual conditionals presents particular challenges for second language learners due to their syntactic and semantic complexity, with limited research investigating feedback effectiveness for this structure. This gap limits theoretical understanding of how different feedback types engage cognitive processing mechanisms during the acquisition of linguistically complex features. This quasi-experimental study investigated the differential effects of direct and indirect WCF on Turkish EFL learners' acquisition of English past counterfactual conditionals. Ninety-four first-year university students were randomly assigned to three groups: Direct WCF (n=32), Indirect WCF (n=32), and Control (n=30). Using a pretest-posttest design with immediate and delayed posttests, participants completed reconstruction tasks over an eight-week period. The Direct WCF group received explicit corrections with correct forms provided above errors, while the Indirect WCF group received metalinguistic clues requiring self-correction. Results showed that direct WCF demonstrated superior immediate effectiveness, but this advantage diminished at delayed posttest, where both treatment groups performed comparably while significantly outperforming the control group. The findings indicate that direct feedback facilitates immediate accuracy improvement in complex grammatical structures, while both feedback types achieve equivalent long-term effectiveness. These results support instructional approaches that employ direct feedback when immediate accuracy is prioritized and suggest that both feedback types engage cognitive processing mechanisms that support sustained learning of complex grammatical features.
Keywords: past counterfactual conditionals; written corrective feedback; cognitive processing; direct feedback; indirect feedback